2022
DOI: 10.3389/fonc.2022.840886
|View full text |Cite
|
Sign up to set email alerts
|

Treatment, pathological characteristics, and prognosis of pulmonary inflammatory myofibroblastic tumor–a retrospective study of 8 cases

Abstract: ObjectiveInflammatory myofibroblastic tumor (IMT) is a rare disease. We reviewed data from eight patients diagnosed with pulmonary IMT (PIMT) at our hospital with the aim of summarizing and analyzing the characteristics of PIMT to improve our understanding of the disease.MethodsFrom January 2012 to December 2019, eight patients underwent surgical intervention for PIMT at The First Affiliated Hospital of Bengbu Medical College. Resected tumors were subjected to pathological and immunohistochemical analyses. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…However, reports indicate that mediastinal lymph node involvement was present in some patients with PIMT undergoing intraoperative resection ( 15 ). Additionally, some researchers suggest lymph node dissection for confirmed IMT cases ( 16 ). In this specific case, the patient's IMT diagnosis had been established before undergoing surgery; accordingly, lymph node dissection was performed, and no abnormalities were detected.…”
Section: Discussionmentioning
confidence: 99%
“…However, reports indicate that mediastinal lymph node involvement was present in some patients with PIMT undergoing intraoperative resection ( 15 ). Additionally, some researchers suggest lymph node dissection for confirmed IMT cases ( 16 ). In this specific case, the patient's IMT diagnosis had been established before undergoing surgery; accordingly, lymph node dissection was performed, and no abnormalities were detected.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, pathological features and IHC tests are viewed as standard procedures to confirm the presence of IMT [ 29 ]; however, those with ALK - expression are still difficult to identify, and can be easily confused with similar diseases, such as pseudotumors [ 22 ]. In 2022, Zhu et al reported their experience in treating eight patients with pulmonary IMT, and proposed that vimentin and SMA may be important markers for diagnosing IMT [ 119 ]. The accuracy of this result needs to be tested in larger studies, but it still brings hope for IMT diagnosis, even with negative ALK expression.…”
Section: Future Challengesmentioning
confidence: 99%